THE INFLUENCE OF DISCOUNTS, PRODUCT COMPLETENESS, AND LOCATION AGAINST CONSUMER PURCHASE DECISION (VIA GOOGLE FROM): STUDY AT BOOK SALES CENTER KOMPLEK TAMAN PINTAR YOGYAKARTA - Akbar, Aly (Journal of Economicate Studies, 2017)
This article discusses consumer purchase decisions that can be affected by discounts, product completeness, and location. Respondents in this study as many as 100 people. Data were collected using questionnaires in the form of questionnaires. Data analysis technique used is multiple linear regression analysis. The results of this study indicate that the discount variables (X1), product completeness (X2), and location (X3) have a simultaneous positive influence on consumer purchase decision (Y). Based on the results of the data analysis obtained R square value is 0,544, this means 54.4% consumer purchases affected by discount variables, product completeness, and location magnitude influence "Strong enough, while the rest of 45.6% influenced by factors or other variables which is not researched. The results of this study also indicate that the discounted variable (X1), product completeness (X2), and location (X3) have a partially positive effect on consumer purchase decision (Y). Based on the results of the analysis of the data obtained correlation value X1 to Y of 0.526 or 52.6%, it means X1 positively affect the Y with the magnitude of influence "Strong Enough", the correlation X2 to Y of 0.635 or 63.5%, meaning X2 positively to Y with the magnitude of the influence of "Strong", and the correlation value of X3 to Y of 0.417 or 41.7%, meaning X3 positively affect the Y with the magnitude of influence "Strong Enough". So, from the correlation analysis can be known variables that have the most influence on purchasing decisions is variable completeness of the product.